Ochratoxin A induces immunotoxicity by targeting Annexin A1 mediated neutrophil apoptosis in zebrafish - Zheng, Yihong; Liu, Yinuo; Tian, Jin; Liu, Shuhong; Ma, Gaowei; Xie, Yupeng; Zheng, Chenhua; Wu, Zekai (Frontiers in Immunology, 2025)
IntroductionOchratoxin A (OTA) is a toxic secondary metabolite produced by Aspergillus and Penicillium species, posing a significant threat to global food safety. Previous studies have demonstrated the diverse toxic effects of OTA, including hepatotoxicity, nephrotoxicity, and carcinogenicity. However, limited understanding exists regarding its immunotoxicity and the underlying mechanisms, particularly in relation to innate immunity.MethodsZebrafish embryos were exposed to varying concentrations of OTA to assess its impact on embryonic development, innate immune cell formation, and immune response. Transcriptome sequencing analysis was performed to identify changes in gene expression. Additionally, the potential therapeutic effect of aesculetin was evaluated.ResultsOur results demonstrated that exposure to OTA inhibited embryonic development and induced malformations in a concentration-dependent manner. Additionally, OTA exposure led to a significant reduction in the number of neutrophils and macrophages, indicating compromised formation of innate immune cells. Furthermore, OTA exposure hampered the immune response during zebrafish fin regeneration, as evidenced by the diminished migration of neutrophils and macrophages to the wound area. Transcriptome sequencing analysis identified significant up-regulation of the anxa1a and anxa1d-mediated apoptosis signaling pathway in neutrophils following OTA treatment. Notably, administration of aesculetin, known for its anti-apoptosis activity, effectively attenuated the immunotoxic effects induced by OTA.DiscussionThese findings provide valuable insights into the immunotoxicity of OTA while highlight the potential therapeutic strategy using aesculetin for mitigating immune dysfunction caused by OTA.